Mandatory health insurance for the informal sector in Tanzania—has it worked anywhere! - Mori, Amani Thomas (Frontiers in Health Services, 2023)
Many countries in sub-Saharan Africa are struggling to expand voluntary health insurance schemes to raise finances toward achieving universal health coverage. With more than three-quarters of the population without any insurance, the government of Tanzania has unsuccessfully tried to pass a Bill proposing a mandatory, nationwide scheme to cover the large and diverse informal sector. The Bill proposed an annual premium of ∼150 USD for a household of six or 65 USD per person. Studies in Tanzania and Kenya have shown that the majority of people in the informal sector are unwilling and unable to pay premiums as low as 4 USD, mostly due to poverty. Mandatory health insurance for the informal sector is not common in this region, mostly because it is difficult to enforce. Successful insurance schemes have included significant subsidies from tax revenues. Tanzania should not seek to raise funds for health through an unenforceable insurance scheme but rather should consider a largely tax-funded scheme for the informal sector. Contributions through low-cost voluntary schemes can enhance social contracts, reduce out-of-pocket expenditure, and promote efficient utilization. In addition, progressive health taxes should be imposed on harmful products (tobacco, alcohol, sugary drinks, etc.) to raise more funds while addressing the increasing burden of non-communicable diseases. Furthermore, efficiency in the use of scarce health resources should be promoted through realistic prioritization of public services, the use of Health Technology Assessment, and strategic purchasing.